Definition
The square root of an expression in R3 is made of the roots of the individual Opposite Values with the signs remaining constant.
Square of an Expression
Given the generic expression (a? + bi? + cj?):
- (a? + bi? + cj?)2 = a2? + a?*bi? + a?*cj? + bi?*cj? + bi?*a? + b2i? + cj?*bi? + c2j? + cj?*a?
Note that as a result of the Zero Rules of Rotation a??b?? + b??a?? = 0, so
- (a? + bi? + cj?)2 = a?2 + bi?2 + cj?2
This shows that the square of an expression is the square of the individual Opposite Values, therefore the square root of an expression is the square root of the individual Opposite Values.
R3 Square Root Example
Firstly, square (3v + 4i^ + 5jv) using long multiplication.
3v + 4i^ + 5jv
3v + 4i^ + 5jv
=============
9v + 12jv + 15iv
20v + 12j^ + 16i^
20^ + 25jv + 15i^
==============
9v + 16i^ + 25jv
The long multiplication shows that:
- (3v + 4i^ + 5jv )*(3v + 4i^ + 5jv ) = (9v + 16i^ + 25jv ) = (3v + 4i^ + 5jv )2 = (3v2 + 4i^2 + 5jv2 )
- Therefore, √(9v + 16i^ + 25jv ) = (√9v + √16i^ + √25jv ) = (3v + 4i^ + 5jv )
Finding the R3 Square Root using Formula
The square root of any equation is easily solved using the roots of the individual Opposite Values:
- (a? + bi?+ cj?)*(a? + bi?+ cj?) = (9v + 16i^ + 25jv)
- (a? + bi?+ cj?) = (√9v + √16i^ + √25jv)
- (a? + bi?+ cj?) = (3v + 4i^ + 5jv)
Conclusion
Try R3 square roots with our online calculator.
Next: Cube Roots
Previous: Definition